Primary Spinal PNET: A Rare Case with Aggressive Progression. - Gupta, Vijay Kumar; Carvalho, Ajay Sebastin; Shekhawat, Nagendra Singh; Vyas, Yelda; Gupta, Ekata (Nepal Journal of Neuroscience, 2024)
PNET of spine are extremely rare, it represent less than 1% of spinal tumors. They are highly invasive and malignant, rapidly growing with grave prognosis. In this case report a 34 yrs lady presented clinically as back ache, urinary symptomps and progressive weakness & spasticty of both lower limbs.After workup patient underwent laminectomy & microscopic gross total excision of tumor, following surgery she improved symptomatically. After confirmation of HPE and IHC she underwent radiotherapy, but she not tolerated chemotherapy and later on tumor recurred and patient succumbed to the disease.